PENYELESAIAN PERKELAHIAN ANTARPEMUDA DESA MALEI TOJO: BAGAIMANA KEPALA DESA MENGAPLIKASIKAN STRATEGI KOMUNIKASI - Lasawedi, Fadel (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
The purpose of this study is to find out the process of resolving fights between teenagers of Malei Tojo Village in terms of communication strategies. Communication strategies have an important role to play in solving fights. The research method used in this study is a qualitative research method in which the results of the research are in the form of narratives obtained from interviews that explain the research problems. The technique of determining the informant used a purposive sampling technique in this case the informant was intentionally determined by the researcher, namely the informants in this study were village apparatus who were directly involved in the process of resolving inter-youth fights. The researcher determined the informant as a sample based on the criteria that stakeholders were involved in the process of completing the fight. The results of this study indicate that the communication strategy carried out by the Malei Tojo Village Government is appropriate. That is by using communication planning by formulating objectives to complete fights, and determining communicators. Although the handling of the village apparatus was still relatively weak, it was to settle the fight between the teenagers of Malei Tojo Village and The Village Government had mediated and signed a peace agreement..